Small molecule inhibitors as adjuvants in cancer immunotherapy: enhancing efficacy and overcoming resistance - Wu, Xiaolin; Feng, Nuan; Wang, Chao; Jiang, Hongfei; Guo, Zhu (Frontiers in Immunology, 2024)
Adjuvant therapy is essential in cancer treatment to enhance primary treatment effectiveness, reduce adverse effects, and prevent recurrence. Small molecule inhibitors as adjuvants in cancer immunotherapy aim to harness their immunomodulatory properties to optimize treatment outcomes. By modulating the tumor microenvironment, enhancing immune cell function, and increasing tumor sensitivity to immunotherapy, small molecule inhibitors have the potential to improve patient responses. This review discusses the evolving use of small molecule inhibitors as adjuvants in cancer treatment, highlighting their role in enhancing the efficacy of immunotherapy and the opportunities for advancing cancer therapies in the future.